AN EXPERIENCE OF PERCUTANEOUS PERITONEAL DRAINAGE IN HIGH-RISK PERFORATED PERITONITIS IN GENERAL SURGICAL WARD OF TERTIARY CARE HOSPITAL LAHORE, PAKISTAN - Asghar, Mohammad Sohail; Kaleem, Ahmad; Zaman, Balakh Sher; Afzal, Ameer; Asghar, Mohammad Sohaib; Rijal, Sushil (Journal of Ayub Medical College Abbottabad, 2021)
A Background: Although conservative treatment has shown a good reduction in mortality and morbidity the majority of patients still need definitive surgery to get rid of the disease completely. It is of note that immediate laparotomy in high-risk patients who have a prolonged history or have multiple comorbidities or in organ failure is not advisable as it is associated with higher morbidity and mortality, besides improved postoperative intensive care. Methods: We categorized these high-risk patients based on their comorbidities and then performed percutaneous peritoneal lavage to reduce the septic load from the peritoneal cavity before performing the definite procedure. Results: Out of the high-risk patients who survived after the PPD and underwent definitive surgery, 61% survived (n=8/13) while the rest of these, 38.5% expired (n=5). Conclusion: Percutaneous peritoneal drainage initially instituted in high-risk patients to optimize their pre-op condition significantly, improves the outcome and has better results than to operate on such patients straightaway.